Analysis of the Incidence of the Tax on Profits in a Credit and Service Cooperative - de Dios Parrera, Yenny; Fernándes Andrés, Ana; Rodríguez Pérez, Héctor (InJEBA : International Journal of Economics, Business and Accounting, 2024)
The examination of tax compliance expenses is becoming more relevant, revealing a complex challenge that involves both national and international fiscal policies. This matter is closely linked to tax evasion and avoidance, and its consequences could distort taxpayers' economic choices. Against this background, the study focuses on the impact of profit tax on the operational outcomes of the 'Fortalecida Abel Santamaría Cuadrado' Credit and Services Cooperative, which operates within the sugarcane sector in Camagüey, Cuba. The research uses both qualitative and quantitative methodologies to investigate this issue. The study aims to provide a detailed understanding of how tax compliance costs affect the cooperative in question by implementing a tripartite procedure that uses mathematical techniques and relative frequency analysis. A key finding from this investigation is the negative impact resulting from the exclusion of advance salary payments as deductible expenses in tax calculations. This finding highlights a critical area for fiscal policy reform as the policy oversight is identified as a source of financial strain for the cooperative. The implications of this discovery are far-reaching, indicating that similar cooperatives and businesses within Cuba (and possibly in comparable economic contexts) may also be experiencing analogous fiscal burdens. Based on these insights, the study recommends the creation of customized methodologies to accurately measure tax compliance costs in the Cuban context. These methodologies should consider the distinctive socio-economic and regulatory features that define the Cuban economy, allowing for more precise evaluations of tax-related burdens on businesses. Furthermore, this research invites broader contemplation on the intersection of tax policy and business sustainability, particularly within sectors that are crucial to national economies but may be vulnerable to strict tax regimes. It emphasizes the need for a balanced approach to tax legislation that protects revenue interests without impeding economic vitality.